Navigating bioethical frontiers: critical concerns in biobanking - Salma Darmayanti; Nuke Ayu Febryana; Zafrullah, Adila; Novian Wildan Rosyidi; Isna Maulida Hanum; Dellarious Benefit Yubaidi (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2026)
A biobank constitutes a systematically organized collection of biological specimens, accompanied by corresponding data and information. These specimens encompass a range of materials such as genetic matter (RNA, DNA, cDNA), blood, serum, plasma, urine, tissue and others. Particularly valuable in longitudinal cohort studies, biobanks facilitate the accumulation of samples over extended durations. This is made feasible by the storage facilities within biobanks, which ensure the preservation of specimen quality over time. However, the utility of biobanks across diverse domains brings to the fore a spectrum of ethical dilemmas, encompassing aspects like informed consent, confidentiality, ownership, property rights, commercialization, feedback mechanisms, and re-contact procedures. Informed consent stands as a cornerstone in a biobank operation. Studies indicate a preference for broad consent due to the forward-looking nature of biobank research and its alignment with prevailing ethical standards. Concurrently, the establishment of a tailored regulatory framework becomes imperative to uphold robust ethical oversight, while also accommodating the values of participants. Addressing concerns regarding ownership, property rights, and commercialization entails the formulation of comprehensive agreement forms detailing donor identity, sample type, intended usage, and potential commercial prospects. Furthermore, ensuring adherence to data confidentiality and individual privacy mandates equips researchers and biobank personnel with ethics training. Regular monitoring and evaluation serve to verify compliance with confidentiality regulations. In instances of noteworthy findings, the biobank can provide feedback or initiate re-contact, with protocol adjustments made in alignment with ethical principles. Consideration may also be given to re-consent procedures as deemed necessary. These protocols may be integrated into the original informed consent documentation, with oversight responsibilities vested in the ethics committee of each biobank.